Description of three new species of Amphitritides Augener, 1922 (Terebellida, Annelida) from the coast of Namibia (South West Africa) - Bick, Andreas; Zettler, Michael L. (Zootaxa, 2024)
Three new terebellid species with two pairs of arborescent branchiae, serrated notochaetae with bulbous wings and avicular uncini in completely separate double rows are described from the Namibian coast, SW Africa, found during different expeditions between 2004 and 2022. These species were assigned to the genus Amphitritides, A. jirkovi sp. nov., A. namibiensis sp. nov. and A. skeletonensis sp. nov. The main diagnostic characters of these species are discussed, especially in the light of the ongoing discussion of synonymising Amphitritides with Amphitrite and Paramphitrite. The features of the three newly described species are compared in a table. An identification key for all known species of Amphitritides is also provided.